Social vulnerability of fishing communities in the southern Cape to change, including additional pressures of COVID-19 - Netshithuthuni, Humbelani (Department of Biological Sciences, 2026)
Marine systems are critical for providing support to the lives and livelihood of millions of people including small-scale fishers (SSFs). However, these communities are faced with many challenges such as resource scarcity, climate change and variability, policy and regulation and the more recent COVID-19 pandemic. This dissertation examines the social vulnerabilities of SSFs in the southern Cape, particularly in the two fishing towns of Bitouville and Melkhoutfontein, to better understand how challenges impact the ability of SSFs to support their livelihoods and how this has changed over the last 10 years. This research made use of a mixed-method technique that included both qualitative and quantitative aspects, drawing on the Global Understanding and Learning for Local Solutions (GULLS) survey that was first implemented in 2013/14 and amended to suit the local context of the southern Cape, which was administered through face-to-face interviews in 2023. Social vulnerability scores were calculated in line with the GULLS framework to gain a deeper insight into the vulnerabilities faced by SSFs and how these have evolved over the last decade. In both Bitouville and Melkhoutfontein communities, vulnerabilities of SSFs were exacerbated by the more recent COVID-19 pandemic, which led to the loss of income sources and available sea days, which in turn contributed to food insecurity. Regarding the evolution of the drivers of changes in 2013/14 and 2023, the results of this study revealed an increase in the social vulnerability scores in both Bitouville and Melkhoutfontein over time as a result of increased exposure to challenges linked to resource scarcity, climate change and variability, and policy and regulation. For example, the continued delay in the implementation of South Africa's small-scale fishing policy (SSFP) has contributed to increased vulnerability as this impacts SFFs' access to fishing rights. The results also revealed that SSFs in Bitouville faced more vulnerabilities compared to their counterparts in Melkhoutfontein, which was attributed to their higher social dependency on fishing, limited livelihood opportunities, higher exposure to environmental changes, and lower adaptive capacity. The vulnerability of these two fishing communities is thus increasing due to compounding stressors such as resource scarcity, climate variability, the COVID-19 pandemic and policy and regulation. This research highlighted the importance of improving the adaptive strategies of SSFs, as limited improvement in these strategies places the livelihoods of these fishing communities at greater risk and exacerbates vulnerabilities in the important, livelihood-intensive southern Cape fisheries.